2017
DOI: 10.1080/1828051x.2017.1404945
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3-nitrooxypropanol as feed additive for mitigating enteric methane emissions from ruminants: a meta-analysis

Abstract: This study aimed to perform a meta-analysis on the effect of 3-nitrooxypropanol (3-NOP) on enteric methane (CH 4 ) emissions from ruminants. A total of 12 in vivo studies from 10 articles were integrated into a database. Ruminant species included were dairy cows, beef cattle and sheep. Concentration of 3-NOP in diets varied from 0 to 280 mg/kg dry matter intake (DMI). Parameters included were CH 4 emissions, rumen fermentation, microbial population, nutrient digestibility and animal performance. Meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 29 publications
7
68
2
8
Order By: Relevance
“…In the present study, a meta-analysis, based on the database including all experiments, revealed that NOP supplementation linearly decreased total VFA concentration and proportion of acetate, on the other hand linearly increased proportion of other individual VFAs, which was similar with a previous meta-analysis study [26]. On the other hand, NOP supplementation had different an effect intensity on total VFA and individual VFA proportion depending on animal type, although CH 4 emissions (g/kg DMI) were decreased with increasing levels of NOP regardless of animal type.…”
Section: Ruminal Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, a meta-analysis, based on the database including all experiments, revealed that NOP supplementation linearly decreased total VFA concentration and proportion of acetate, on the other hand linearly increased proportion of other individual VFAs, which was similar with a previous meta-analysis study [26]. On the other hand, NOP supplementation had different an effect intensity on total VFA and individual VFA proportion depending on animal type, although CH 4 emissions (g/kg DMI) were decreased with increasing levels of NOP regardless of animal type.…”
Section: Ruminal Parameterssupporting
confidence: 90%
“…The present study conducted a meta-analysis using total 14 in vivo studies published from 2014 to 2019, and the meta-analysis showed that supplementation of NOP was effective to a significant linear decrease in CH 4 yield (g/kg DMI), regardless of animal type compared with those fed a diet without NOP. It is similar with a result from Jayanegara et al [26] who reported NOP supplementation had an effect of CH 4 mitigation regardless of type of CH 4 unit (CH 4 g per BW, DMI, milk, DMI, and digested OM). Dijkstra et al [27] revealed that NOP supplementation has stronger CH 4 mitigation effects in dairy cattle than in beef cattle, when a meta-analysis was analyzed using 9 in vivo studies from 2014 to 2018 [16][17][18][19][20][21][22][23][24].…”
Section: Methane Mitigationsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, reductions in methane emissions do not always result in a redirection of energy, leading to enhanced animal production. For example, 3-nitrooxypropanol (3-NOP) has been shown to reduce methane emissions by up to 30% (Hristov et al, 2015 ; Jayanegara et al, 2018 ). However, a meta-analysis of all available animal data following supplementation with 3-NOP only shows modest increases in animal production, possibly due to decreased volatile fatty acid (VFA) produced from breakdown of cellulose and increased H 2 production; both processes requiring energy input (Jayanegara et al, 2018 ).…”
Section: Global Agricultural Challengesmentioning
confidence: 99%
“…Large variation in response to addition of NOP was reported; namely, between a decrease of 84.3% (Vyas et al, 2016) and an increase of 7.1% (Vyas et al, 2018) in CH 4 production compared with the control diet. In a recent meta-analysis, Jayanegara et al (2018)…”
Section: Short Communicationmentioning
confidence: 99%